Changes of urine dihydroxyphenylglycol to norepinephrine ratio in children with attention-deficit hyperactivity disorder (ADHD) treated with atomoxetine - Montoya, Alonso; Escobar, Rodrigo; García-Polavieja, María J; Lachno, D Richard; Alda, José Ángel; Artigas, Josep; Cardo, Esther; García, Marta; Gastaminza, Xavier; Gilaberte, Inmaculada (Journal of child neurology, 2011)
This study investigated changes in the urine dihydroxyphenylglycol to norepinephrine ratio in patients with attention-deficit hyperactivity disorder (ADHD) treated with atomoxetine. The possible relationship with clinical response was also explored. Newly ADHD diagnosed, treatment-naïve children or adolescents were double-blindly randomized (2:1) to atomoxetine (n = 28) or placebo (n = 13). The dihydroxyphenylglycol to norepinephrine ratio decreased in both groups, showing significantly greater changes with atomoxetine than with placebo at week 6 (-42% versus -14%; P = .001), when dosed at 1.2 mg/kg/day, than at week 2 (-20% versus -2%; P = .118) with a dose of 0.5 mg/kg/day. Although the significant dihydroxyphenylglycol to norepinephrine ratio decrease with atomoxetine indicated norepinephrine transporter blockade, no association with ADHD clinical response (ADHD Rating Scale-IV-Parent:Investigator) was found. Therefore, dihydroxyphenylglycol to norepinephrine ratio might be a useful pharmacodynamic/pharmacokinetic biomarker, although not sufficiently sensitive to predict clinical efficacy. It remains a possibility that this ratio might have value to facilitate personalized atomoxetine pharmacotherapy in ADHD patients.